A simultaneous container assignment and ship scheduling optimisation model in container shipping - Christine Natalia; Michael Holine; Agustinus Silalahi (Asian Journal of Shipping and Logistics (AJSL), 2021)
Maritime transportation is preferred over other transportation forms for trade and has seen a significant increase worldwide. One of the problems that often occur in maritime transportation is the high cost because vessels' availability and capacity will always be the same while the demand tends to increase and erratic for each period. A mathematical model was developed in this study to determine the optimal value of container cargo and shipping frequency simultaneously to minimise the shipping cost for each voyage. To solve the container cargo optimisation problem, we presented an integer linear program, while for the scheduling, we used the greedy algorithm. Microsoft Excel Solver and LINDO software were used to solve the problem in this study. We provided computational calculations to simulate our mathematical model. The results show that the developed model produces feasible solutions for all scenarios due to the objective function and the constraints. Overall, our scheduling results can reduce the shipping frequency. The optimal solution value of container cargo and the scheduling results for each scenario are different because the total number of transported containers for each scenario is different.
Keywords: 650; Maritime transportation; Container assignment model; Scheduling; Linear programming; The greedy algorithm